Psychological Resilience of Migrant Workers in Thailand: Between Challenges and Adaptation in the Destination Country - Farmawati, Cintami; Muniroh, Siti Mumun; Hayeesama-ae, Solihah (Populasi, 2025)
Psychological resilience is an important factor in determining the mental well-being of migrant workers. Migrant workers are people who migrate or have migrated from one country to another who will be employed by anyone other than themselves. This study aims to determine the factors which influence the psychological resilience of migrant workers in Thailand, and how they adapt to challenges in the new environment. This study is a qualitative study. The subjects in the study were three migrant workers in Thailand. Data collection methods used were interviews, observation and documentation. Data analysis used was data reduction, data presentation, and drawing conclusions. The results of the study showed that the factors influencing the psychological resilience of migrant workers in Thailand can be grouped into two, specifically internal factors and external factors. These internal factors are spirituality, self-efficacy, optimism, self-esteem, hope, and hardiness. External factors are social and family support. Meanwhile, the description of the adaptation of migrant workers in Thailand to the challenges in the new environment can be grouped into three strategies:  social adaptation, economic adaptation and cultural adaptation.